(untitled) (INNOVATIVE ECONOMY, 2021)
Bahlei R.R. FORMATION AND ENSURING ECONOMIC SECURITY OF CORPORATE STRUCTURES IN AN UNSTABLE ENVIRONMENT Purpose. The aim of the article is the consideration of theoretical and organizational aspects of forming an effective system of economic security of corporate structures. Methodology of research. A dialectical method of cognition of economic laws, a systematic approach to the study of economic phenomena, as well as a monographic, abstraction, abstract and logical methods were used to achieve this goal. The methodological basis of the study was theoretical developments of scientists in the analysis of the essence and economic content of the category “economic security”. The monographic method was used in the study of literature on economic security, system and analytical – in processing the information. Findings. The meaning of the concept “economic security of the enterprise” and “economic security of the corporation” is defined. The priority directions in ensuring security and the principles on which the system of ensuring economic security of the corporation is based are highlighted. The mechanism of formation of economic security of the corporation which is based on various approaches and indicators for prevention and levelling of their dangerous displays is offered. Originality. Approaches to the interpretation of scientific definitions of “corporation”, “economic security of the enterprise” are generalized, which allowed to define the concept of “economic security of the corporation”, to form a methodological basis for corporate security of companies; outline the priorities, goals and key objectives of ensuring the economic security of corporations while identifying external and internal threats to the security of corporate structures. Practical value. The obtained results of the study will help increase the efficiency of formation and development of economic security of corporations and will serve as a basis for further research in this area. Key words: corporation, economic security, principles, system of providing economic security.